Analisis Pengendalian Persediaan Bahan Kimia Tawas dengan Metode EOQ dan JIT Pada Perumda Giri Tirta Gresik - Salman Alfi Yuganta; Hidayat Hidayat; Moh. Jufriyanto (Universitas Islam Raden Rahmat, Malang, 2024)
Perumda Giri Tirta is a BUMD company owned by the Gresik Regency Government which is engaged in drinking water management services. Perumda Giri Tirta requires alum material to produce with orders 15 times a year with a total usage of 1,588,215 kg at a cost incurred by the company of Rp. 22,182,299. When compared with 2 inventory control methods, namely Economic Order Quantity and Just In Time, a more efficient calculation will be produced. The results of calculations with the EOQ method the frequency of ordering is 7 times at a cost of Rp. 17,352,969 or 88% more efficient than the cost according to Perumda Giri Tirta's policy. Meanwhile, with the JIT method, orders were made 3 times at a cost of Rp. 6,573,094 or 95% less than the cost according to Perumda Giri Tirta's policy.